DARI TEKNOLOGI KE KEADILAN: MENGKAJI PENGALAMAN PENGGUNA SIPRAJA DAN DIGIPAY DALAM INOVASI PELAYANAN PUBLIK - Faradina Selsa Putri; Ani Yuni Setyowati; Akhmad Irham Faujik (Jurnal Kebijakan Pemerintahan, 2025)
Public service innovations, such as SIPRAJA and DigiPay, have become one of the government's strategies to improve service efficiency by adapting to technological developments. This research is a systematic literature study that analyzes and interprets findings from previous qualitative research through a phenomenological lens to understand users' experiences in public services.The results of the analysis have revealed that public service innovations have increased the accessibility and efficiency of public services for the community, although gaps hamper them in digital literacy and infrastructure. This leads to varying levels of community satisfaction and perceptions of justice. Some people are satisfied and find it easy to access services, while others feel the opposite due to a less inclusive design that causes a sense of injustice. In terms of community participation in public service innovation, it is still consultative and has not yet reached a collaborative level. This research highlights the need for service design based on co-creation, digital literacy training, and infrastructure equity to achieve equity of access and satisfaction for communities. This research also highlights the importance of user experience-based evaluation in the digital transformation of public services, emphasizing that public innovation cannot be separated from citizens' subjective experience.   Keywords: Phenomenological approach, Public service innovation